ASSESSMENT OF YIELD LOSS DUE TO NIGER (GUIZOTIA ABYSSINICA (L.F.) CASS.) LEAF SPOT CAUSED BY ALTERNARIA ALTERNATA (FR.) KEISSL - S. S. KANSARA,; A. N. SABALPARA, (The Bioscan, 2015)
Loss in niger(Guizotiaabyssinica (L.f.) Cass.) caused by Alternaria leaf spot disease Alternaria alternata (Fr.) Keissl., is a major concern of niger growers. Leaf spot is considered a most injurious disease of niger in south Gujarat, resulting in severe loss especially to susceptible niger cultivars. The disease became epidemic during rainy season, caused heavy loss in grain yield.The avoidable loss of grain yield was estimated to be 34.27 % due to leaf spot disease. With the proper protection measures, 71.40 per cent leaf spot disease can be controlled. Niger crop can be protected from leaf spot disease by giving the seed treatment with mixed formulation of carbendazim (12 %)+ mancozeb(63 %) (Saaf 75 % WP) @ 2.5 g/kg seeds and two sprays of Saaf 75 WP @ 0.2 %, 1 st at appearance of the disease and 2 nd at 15 days after 1st spray.